The Effect Of Social Media-Based Promotion On Tourism Decisions-Making - Miska Irani TARIGAN; Anitha Paulina TINAMBUNAN (Indonesia Strategic Sustainability, 2022)
This study aimed to determine the social media promotion effect on travel decisions. This research design is survey research. The population in this study was people who searched for tourist information and made travel decisions. The sampling techniques in this study used purposive sampling with 110 samples. The data collection technique used a questionnaire tested for validity and reliability. The data analysis technique used to answer the research hypothesis is a simple regression test. This research indicates that there was a positive effect of social media promotion on travel decisions. The results of this study were the coefficient of determination (R2) which is 66.2%, the results of the Fcount test are 211.612 with a significance value of 0.000, then the t-count results are 14.547 with a significance value of 0.000. These results show that promotion through social media simultaneously and significantly influences travel decisions.